2012
DOI: 10.1111/j.1540-8159.2012.03498.x
|View full text |Cite
|
Sign up to set email alerts
|

Transseptal Left Ventricular Lead Placement Using Snare Technique

Abstract: The use of a GooseNeck snare via a deflectable transseptal sheath represents a reliable alternative method for endocardial LV lead placement in patients with failed CS LV lead implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…In previous studies, several techniques for transseptal LV endocardial pacing for CRT have been proposed in patients for whom routine transvenous LV pacing is infeasible. Most approaches previously described have used dual access in which the transseptal puncture was performed from the femoral vein, followed by: (1) dilating the transseptal puncture, then picking the hole using a deflectable mapping catheter or other preshaped catheter/wire introduced from the subclavian vein and railroading a sheath into the LA through which the LV lead is delivered; (2) implanting the lead from the femoral vein, then grabbing the lead connector with a snare introduced through the subclavian vein and pulling it out through the vein to be connected to the generator in the pectoral area; (3) introducing the lead from the subclavian vein, then grabbing it with a snare introduced from the femoral vein and forcing it through the septum over a wire introduced earlier into the LA; or (4) grabbing the transseptal needle introduced through the femoral vein with a snare introduced from left subclavian vein, then forcing it through the septum into the LA and railroading a sheath to deliver the LV lead . Lately, the ALSYNC study reported a system that abandoned the femoral access.…”
Section: Disscussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, several techniques for transseptal LV endocardial pacing for CRT have been proposed in patients for whom routine transvenous LV pacing is infeasible. Most approaches previously described have used dual access in which the transseptal puncture was performed from the femoral vein, followed by: (1) dilating the transseptal puncture, then picking the hole using a deflectable mapping catheter or other preshaped catheter/wire introduced from the subclavian vein and railroading a sheath into the LA through which the LV lead is delivered; (2) implanting the lead from the femoral vein, then grabbing the lead connector with a snare introduced through the subclavian vein and pulling it out through the vein to be connected to the generator in the pectoral area; (3) introducing the lead from the subclavian vein, then grabbing it with a snare introduced from the femoral vein and forcing it through the septum over a wire introduced earlier into the LA; or (4) grabbing the transseptal needle introduced through the femoral vein with a snare introduced from left subclavian vein, then forcing it through the septum into the LA and railroading a sheath to deliver the LV lead . Lately, the ALSYNC study reported a system that abandoned the femoral access.…”
Section: Disscussionmentioning
confidence: 99%
“…In contrast, atrial transseptal LV endocardial pacing is less invasive and not restricted by access limitation. A number of techniques with varying difficulty and complexity have been described . We herein report a simple, safe and effective approach of atrial transseptal LV lead implantation using arteriovenous loop technique in a patient for whom transvenous LV lead implantation had failed.…”
Section: Introductionmentioning
confidence: 99%
“…TOE guided transseptal puncture can help in endocardial left ventricular lead placement in patients with unfavorable venous anatomy or failed epicardial lead placement [44,45]. TOE guided transseptal puncture can help in endocardial left ventricular lead placement in patients with unfavorable venous anatomy or failed epicardial lead placement [44,45].…”
Section: Procedural Guidancementioning
confidence: 99%